Vegetation of Central Asia and Environs (Springer International Publishing, 2018)
Central Asia is a large and understudied region of varied geography, ranging from the high passes and mountains of Tian Shan, to the vast deserts of Kyzyl Kum, Taklamakan to the grassy treeles steppes. This region is faced with adverse conditions, as much of the land is too dry or rugged for farming. Additionally, the rich specific and intraspecific diversity of fruit trees and medicinal plants is threatened by overgrazing, oil and mineral extraction, and poaching. Countless species from the approximately 20 ecosystems and 6000 plant taxa are now rare and endangered. Traditional vegetation studies in this region are far from adequate to handle complex issues such as soil mass movement, soil sodicity and salinity, biodiversity conservation, and grazing management. However, data analysis using a Geographical Information System (GIS) tool provides new insights into the vegetation of this region and opens up new opportunities for long-term sustainable management. While vegetation planning can occur at a property scale, it is often necessary for certain factors, such as salinity, to be dealt with on a regional scale to ensure their effective management. GIS increases the effectiveness and accuracy of vegetation planning in a region. Such regional planning will also greatly increases biodiversity values. This book systematically explores these issues and discuses new applications and approaches for overcoming these issues, including the application of GIS techniques for sustainable management and planning. Professional researchers as well as students and teachers of agriculture and ecology will find this volume to be an integral resource for studying the vegetation of Central Asia.